Analisis Pengaruh Kepemimpinan Transformasional Dan Budaya Organisasi Terhadap Motivasi Dosen (Survey Pada Universitas Swasta Di Provinsi Riau) - Ahadi, Nopri (Jurnal Rumpun Ilmu Ekonomi, 2023)
Transformational Leadership, through its emphasis on vision, inspiration, and personal attention, aligns closely with positive organizational cultures, creating an environment where lecturers and staff feel valued and empowered. This alignment encourages a sense of ownership and commitment towards the university's goals, fostering an atmosphere where innovation and creativity are nurtured. As these elements become ingrained within the organizational fabric, they contribute to building a strong community spirit, where collaboration and shared success become the norm. Consequently, in private universities where transformational leadership and a supportive organizational culture are prevalent, the result is not only high motivation among lecturers but also an enhanced learning experience for students. This synergy between leadership and culture acts as a catalyst for academic excellence, positioning the university as a beacon of innovation and quality education.